Potential and economic efficiency of the use of remains crops - Кулик, М. І.; Пасічніченко, О. М. (Scientific Progress & Innovations, 2016)
The article contains the level of productivity of primary products (grain, seeds) and the potential (common and power) of plant crop residues was calculated. The economic efficiency of production by-products – plant remains (straw and stalks) of winter wheat, corn, sorghum and sunflower were presented. The results confirm their high return and profitability as raw materials for biofuel.